Development of ethnomathematics-based learning tools to achieve mathematical literacy skills of junior high school students - Anisa Mita Ristanti; Nila Mareta Murdiyani (Universitas negeri Yogyakarta, 2021)
The purpose of this research is to develop an ethnomathematics-based learning tool to achieve mathematical literacy skills of junior high school students with valid, practical, and effective qualifications on polyhedron subjects. This research used a mixed research method with ADDIE research development procedures. This study involved the eighth graders of SMP Negeri in Wonosobo Regency, Centra1 Java as the research objects. The research instruments were validation sheets, student response questionnaires, observation sheets of learning implementation, and test questions of mathematical literacy skills. The results showed that: 1.) The learning tool was declared valid, indicated by the result of the lesson plan assessment obtaining a score of 120, which was classified in the very good criteria, and the results of the student worksheet assessment obtaining a score of 159, which was included in the very good criteria; 2.) The learning tool was declared practical as indicated by the score on the student response questionnaire of 65,13, which was included in the good criteria. The percentage of learning implementation was of 89%, included in the very good criteria; and 3.) The learning tool was declared effective as indicated by an increase in students’ pretest and posttest scores, from 64,22 to 83,67, and 84% of students’ completeness on the posttest, having met the minimum criteria of good.